Pengaruh Komunikasi Organisasi Dan Kepemimpinan Terhadap Kinerja Pegawai Pada PT. Teknologi Ahura Quasantra - Anggraeni, Frida Nur; Ramly, Amir Tengku; Kirbandoko, Kirbandoko (Jurnal Manajemen, 2021)
The problem which is used as the object of this research is two independent variables and one dependent variable, namely organizational communication and leadership with employee performance. This study aims to: (1) Analyze and determine the effect of organizational communication on employee performance, (2) Analyze and determine the effect of leadership on employee performance, (3) Analyze and determine organizational communication and leadership together on employee performance, at PT. Ahura Quasantra technology. This type of research is descriptive quantitative analysis. The sample used in this study were all employees of PT. Ahura Quasantara technology. The analytical tool used is multiple linear regression analysis. The results of the study using the SPSS 26 program resulted in three conclusions, namely: 1) there is a very significant effect of organizational communication on employee performance, a significant value of 0.000 is obtained smaller than 0.05 or 0.000 <0.05, 2) there is a very significant influence. The significant value between leadership and employee performance is obtained a significant value of 0.002 smaller than 0.05 or 0.002 <0.05, 3) there is a very significant relationship between organizational communication and leadership together on employee performance. f count is 92,87 bigger than f table of 3.17 or f count> f table is 92,87> 3.17.